2016
DOI: 10.1084/jem.20151255
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF drives regulatory T cell expansion by paradoxically promoting membrane TNF–TNF-RII binding in rheumatoid arthritis

Abstract: Nguyen and Ehrenstein reveal that anti-TNF antibodies paradoxically enhance membrane TNF–TNF-RII interactions to increase Foxp3 expression and confer upon T reg cells the ability to suppress Th17 cells in rheumatoid arthritis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
143
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 44 publications
10
143
2
Order By: Relevance
“…On the contrary, treatment with TNF-α per se has been shown to be beneficial in animal models of autoimmunity, such as RA [38], lupus [110], and IDDM (T1D) [111]. In addition, there are conflicting reports on the influence of TNF-α on the generation and function of Treg cells [112, 113]; some reports emphasize a positive relationship between TNF-α and Treg cell expansion and/or function [112, 114117], while others describe a negative effect of TNF-α on Treg cell number and activity [118120]. There is additional disparity between murine and human Treg cells in regard to the effect of TNF-α on these cells [112, 113].…”
Section: Tnf-α-induced Immune Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, treatment with TNF-α per se has been shown to be beneficial in animal models of autoimmunity, such as RA [38], lupus [110], and IDDM (T1D) [111]. In addition, there are conflicting reports on the influence of TNF-α on the generation and function of Treg cells [112, 113]; some reports emphasize a positive relationship between TNF-α and Treg cell expansion and/or function [112, 114117], while others describe a negative effect of TNF-α on Treg cell number and activity [118120]. There is additional disparity between murine and human Treg cells in regard to the effect of TNF-α on these cells [112, 113].…”
Section: Tnf-α-induced Immune Regulationmentioning
confidence: 99%
“…Additional insight into the impact of TNFR2 on Treg cell activity has been gained from a recent study on adalimumab, an humanized anti-TNF-α antibody [113]. Adalimumab can bind to the mTNF-α on monocytes of RA patients but not healthy controls [113].…”
Section: Tnf-α-induced Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a still incomplete understanding of the mechanism of TNFRSF signaling hampers the development of more effective therapies. For instance, it has only been recently established that TNF receptor II (TNFR2) is an important pathway of regulatory T cell (T reg ) expansion or contraction, even in adult human T cells (5)(6)(7). T regs are important targets for both cancer and autoimmune therapies, and there are several TNFRSF receptors expressed on T reg and other immune cells to regulate their function.…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, it has been shown that therapeutic TNF blockade with the anti-TNF monoclonal antibody adalimumab restores the potency of Treg cell suppression in RA by binding to membrane TNF-a on monocytes and promoting Treg cell expansion through enhanced TNFR2 signaling. 3 In the present study we aimed to establish the role of TNFR2 on Tregs in control of inflammation at multiple levels, by: 1) studying the action of TNF on Treg function in the presence and absence of TNFR2 in vitro, 2) testing the severity of a model of skin inflammation in TNFR2KO mice, 3) evaluating the evolution of TNFR2-expressing Treg from RA patients during anti-TNF treatment. Materials and methods Mice deficient in the TNFR2 gene (TNFR2 KO) and TNFR2 lox/lox mice to conditionally delete TNFR2 specifically in Tregs were used.…”
mentioning
confidence: 99%